PENGUATAN KAPASITAS SOSIAL DAN EKOLOGIS MASYARAKAT DESA WAAI DALAM MENGHADAPI PERUBAHAN IKLIM - Imlabla, Wilma Nancy; Parera, Evelin; Maail, Rohny S.; Aponno, Hendrik S. E. S. (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to strengthen the community’s adaptive capacity through educational and participatory approaches in responding to climate change. The implementation methods included socialization sessions, focused group discussions, training on simple mitigation techniques, and mentoring on natural resource management based on local wisdom. The results showed a significant increase in community awareness and understanding of climate change issues, especially regarding the vital role of protected forests in maintaining ecosystem balance and water resilience. The activity also fostered the formation of a climate care community group that initiated adaptive environmental actions, including tree planting, water source conservation, and integrated waste management. Collaboration among academics, local government, and customary institutions played a key role in strengthening social networks and local institutions as social capital for sustainability. Overall, this PKM activity contributed to building a more resilient, adaptive, and empowered community in Waai Village to face the impacts of climate change at the local level.